Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning 2019
DOI: 10.1007/978-3-030-20062-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Human and Blended Support to Assist Learning About ICT Integration in (Pre-service) Teacher Design Teams

Abstract: The context of this study is the pre-service science teacher education program at the Public Authority of Applied Education and Training (PAAET) in Kuwait. A major problem in the pre-service teacher education curriculum at this institution was how pre-service science teachers were prepared to use ICT in their teaching. To tackle this problem, Technological Pedagogical Content Knowledge (TPACK) was used as a conceptual framework for developing an intervention to prepare students in the science teacher program f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
6
0
4
Order By: Relevance
“…This suggests that attitude changes were influenced by the kind of activities teachers participated in favour of collaborative lesson design activities. The effectiveness of lesson design activities is also reported in multiple studies (Alayyar and Fisser, 2019; Giles, 2019; Guo and Carey, 2008; Lambert and Gong, 2010; Strutchens et al. , 2017; Valtonen et al.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This suggests that attitude changes were influenced by the kind of activities teachers participated in favour of collaborative lesson design activities. The effectiveness of lesson design activities is also reported in multiple studies (Alayyar and Fisser, 2019; Giles, 2019; Guo and Carey, 2008; Lambert and Gong, 2010; Strutchens et al. , 2017; Valtonen et al.…”
Section: Discussionmentioning
confidence: 78%
“…The analysis indicated that the nature of activities across time influences the level of attitudes. This suggests that attitude changes were influenced by the kind of activities teachers participated (Alayyar and Fisser, 2019;Giles, 2019;Guo and Carey, 2008;Lambert and Gong, 2010;Strutchens et al, 2017;Valtonen et al, 2015). Specifically, Hennessy et al (2010) argued that such activities do not only enable the development of attitudes but build a sense of ownership of the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Learning by design is when the PSTs are given an opportunity to select and design the learning materials using digital technologies (Alayyar & Fisser, 2019). These authors assert that the designing skills involve cooperating with the production team to design learning activities and to select appropriate tools and techniques to organise and present the learning materials in different formats.…”
Section: Learning By Designmentioning
confidence: 99%
“…These policies require a comprehensive system aimed at teachers properly integrate ICT, creative programming, algorithmic thinking, game-based and problem-based learning into their teaching practice and mediate its use and impact. Therefore, training, workshops, and courses are essential and urgent to provide teachers with opportunities to learn about effective, appropriate, and intentional use of ICT in their teaching practice (Ihmeideh and Al-Maadadi, 2018;Alayyar and Fisser, 2019). Moreover, in addition to strictly technical skills related to the use of ICT equipment, it is extremely important to shape awareness among teachers about the desirability of using technology in school teaching informatics.…”
Section: Polish School Educational Systemmentioning
confidence: 99%